Predictive role of the dietary inflammatory index on stroke risk among hypertensive patients - Jingru Fan; Yane Yang; Yunjie Yang; Dewei Rui; Shunqi Guo; Meiju Li; Yibing Wang; Yingqing Feng; Chuanwei Zhao (Scientific Reports)
Abstract This study aims to evaluate the association between the dietary inflammatory index (DII) and stroke risk in hypertensive patients. Data were sourced from the National Health and Nutrition Examination Survey (NHANES) spanning 1999–2020, including 23,712 hypertensive patients. DII scores were calculated based on dietary intake data, and stroke diagnoses were determined through self-reported physician diagnoses. The relationship between DII and stroke risk was assessed using multivariable logistic regression models. Dose–response relationships and subgroup differences were explored through stratified analysis and restricted cubic spline (RCS) methods. Key dietary factors associated with stroke were identified using least absolute shrinkage and selection operator (LASSO) regression and incorporated into a risk prediction nomogram model. The model’s discriminatory ability for stroke was evaluated using receiver operating characteristic (ROC) curves. After adjusting for confounding factors, the highest DII quartile was associated with an adjusted odds ratio (OR) of 1.44 (95% CI 1.19, 1.74) for stroke compared to the lowest quartile, and each unit increase in DII was associated with an OR of 1.08 (95% CI 1.04–1.13) for stroke prevalence. The RCS curve demonstrated a nonlinear relationship between DII and stroke, with a turning point at 0.29. The nomogram model based on key dietary factors identified by LASSO regression had an area under the curve (AUC) of 70.93% (95% CI 69.81%–72.06%). There is a nonlinear relationship between DII and stroke risk in hypertensive patients. Given the inherent limitations of a cross-sectional study design, further research is needed to establish causality.